Authentication of Drimys piperita Hook f. Tree Bark Infusion from the Adulteration of Cinnamomum burmannii Nees Ex Bl. using the Combination of UV Spectroscopy and Chemometrics Techniques - Sabela, Vivian Yulias; Laurendy, Chesie; Prarathana, Dicky; Riswanto, Florentinus Dika Octa (Fakultas Farmasi, Universitas Surabaya, 2025)
This study aims to develop a method to authenticate akway bark (Drimys piperita Hook f.) infusion using UV spectroscopy and chemometrics techniques. The background initiative of this study is the consideration of the high economic value of akway bark which may potentially lead to the adulteration of the akway raw materials for traditional medicine. The sample used in this study was akway bark obtained from Manokwari, Papua, Indonesia. Samples of akway bark, cinnamon, and a mixture of both were prepared in the form of powder and then infused. The infusion was examined using UV spectroscopy to obtain the absorption value of each wavelength. Chemometrics techniques including principal component analysis (PCA) and multivariate calibration using principal component regression (PCR) and partial least squares (PLS) regression were carried out during the study. Additionally, computational discrimination using sparse partial least squares discriminant analysis (sPLS-DA) was performed afterwards. A total of 36 distinctive wavelengths were obtained. The absorption values were then used to form a PCA model. The best multivariate calibration model was derived from PCR data processing on the original spectra for both akway and cinnamon bark infusion samples. The AUC-ROC values obtained from the application of the sPLS-DA technique for each sample were 1.000, 0.956, and 0.633 for akway bark, cinnamon, and the mixture of both, respectively. Authentication of akway bark infusion has been successfully conducted on the presence of cinnamon as the adulterant.